Mapping the demand and potential for cycling in Toronto. Issue 4 (1st February 2021) - Young, Mischa; Savan, Beth; Manaugh, Kevin; Scott, James
Abstract: Many municipalities are investing in cycling infrastructure; these efforts increase safety and comfort, and typically occur in central neighborhoods as they have a higher proportion of cyclists. However, targeting cycling investments in neighborhoods with a strong latent demand for cycling, regardless of their current cycling mode share, may also increase cycling adoption. Accordingly, the aim of this paper is to identify areas that present the highest potential for cycling uptake. To this end, we use data from the most recent 2016 Transportation Tomorrow Survey in Toronto and conduct a generalized linear model to uncover the sociodemographic, behavioral, and land use characteristics that influence cycling mode share. We identify areas with a lower cycling mode share than predicted by our model and argue that these present a higher potential for cycling. Governments interested in increasing cycling mode share should consider expanding their efforts and investments beyond central neighborhoods, as those with a latent demand for cycling may also yield positive results for cycling mode share.